Faktor yang Memengaruhi Kejadian Kurang Energi Kronik (KEK) pada Ibu Hamil - Emerensiana Dhiu; Noorce Christiani Berek; Luh Putu Ruliati; Lewi Jutomo; Jacob Matheos Ratu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the factors associated with the incidence of Chronic Energy Deficiency (KEK) in pregnant women in the working area of the Oesapa Health Center. This type of research is cross-sectional with simple random sampling. The results showed that the percentage of pregnant women who experienced CED was 57.3%. Statistical test data showed that there was a significant influence between eating patterns, namely food frequency (p-value 0.015), amount of food (p-value 0.018), type of food (p-value 0.014), education (p-value 0.027), occupation ( p-value 0.038) and knowledge (p-value 0.004) with CED events. In conclusion, diet, education, work and knowledge affect the incidence of SEZ. Keywords: Pregnant Women, Chronic Energy Deficiency